A MOTHER’S STRUGGLE IN LANGSTON HUGHES’S “MOTHER TO SON” - Gibran, Kahfi (LANTERN (Journal on English Language, Culture and Literature), 2016)
This extended essay is concerned with images of a mother’s struggle in Langston Hughes “Mother to Son”. The purpose of this study is to present the struggle through imagery, literature and society. The imagery is chosen as the intrinsic element of literature and society as an extrinsic element of the poem. The study applies a library research method. This study adopts Perrine’s concept of imagery and Wellek and Warren’s concept of literature and society. “Mother to Son” figuratively describes the mother’s struggle which makes a movement in her life to a better life. It is also about how the mother advises her son not to easily give up even the life is getting harder. As a result, this poem describes the mother’s struggle beautifully.